2013
DOI: 10.1097/mca.0b013e3283647a99
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle modification decreases arterial stiffness and plasma asymmetric dimethylarginine level in overweight and obese men

Abstract: Lifestyle modifications reduce arterial stiffness and plasma ADMA concentration in overweight and obese individuals. A decrease in arterial stiffness was associated with a corresponding reduction in plasma ADMA concentrations. These results suggest that reductions in ADMA may be an important mechanism underlying the beneficial effect of lifestyle modification on arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
1
19
0
6
Order By: Relevance
“…This finding is also supported by our previous publications as well as those from another research group [13][14][15]. In obese people, increased circulating cholesterol, triglycerides and insulin are associated with elevated arterial stiffness.…”
Section: -24]supporting
confidence: 79%
See 3 more Smart Citations
“…This finding is also supported by our previous publications as well as those from another research group [13][14][15]. In obese people, increased circulating cholesterol, triglycerides and insulin are associated with elevated arterial stiffness.…”
Section: -24]supporting
confidence: 79%
“…A previous study demonstrated that anti-inflammatory medication decreased arterial stiffness in rheumatoid patients who had high circulating levels of pro-inflammatory factors [12]. We and other research groups have shown that weight-loss caused by lifestyle modifications reduced arterial stiffness in obese individuals [13][14][15][16]. However, there have been no reports regarding obese individuals and the effect of weight-loss on the change in several types of inflammatory factors, as a mechanism for decreased arterial stiffness.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…However, about 46% of primary care patients at risk for diabetes did not do physical activity per week [40]; while two-third of patients with diabetes remain inactive [64]. It has been recommended that moderate to vigorous physical activity can reduce the risk of chronic diseases such as diabetes and its complications [65][66][67]. Health counsellors should address these barriers to increase the patients' adherence to physical activity as the recommendations [41].…”
Section: Discussionmentioning
confidence: 99%